Identification of RFLPs flanking a scald resistance gene on barley chromosome 6 - Abbott, D C; Lagudah, E S; Brown, A H (The Journal of heredity, 1995)
We report the map location of the scald resistance gene, Rrs13, from wild barley (Hordeum vulgare ssp. spontaneum) with respect to RFLP loci on barley chromosome 6 (= 6H). The identification of two RFLP loci (Cxp3 and ABG458) flanking the Rrs13 locus will assist selection for the resistant allele in barley breeding programs.